Changing status of three notothenioid fish at the South Shetland Islands (1983–2016) after impacts of the 1970–80s commercial fishery - Barrera Oro, Esteban; Marschoff, Enrique Ricardo; Abramson, David (Polar Biology)
Owing to commercial fishing during the late 1970s/early 1980s, targeted notothenioid species had become depleted around the South Shetland Islands. Herein we report subsequent changes in the prevalence of three species, Notothenia rossii, Gobionotothen gibberifrons and Notothenia coriiceps in Potter Cove, King George Islands/Isla 25 de Mayo, in a 33-year effort to monitor recovery. N. rossii and G. gibberifrons had been severely impacted by industrial fishing but in offshore waters N. coriiceps had never been commercially fished; however, all three species exhibit similar nearshore habitats and life history. We examined composition in trammel net catches during 2012–2016, augmenting a time series started in 1983. Our inshore results were consistent with those from offshore bottom trawl sampling in 2007 and 2012 around the South Shetland Islands: (1) continued increase in the abundance of N. rossii; (2) further decline in G. gibberifrons recruitment evidenced by low proportions of juvenile fish; and (3) a high abundance of N. coriiceps. Reasons for lack of recovery in G. gibberifrons remain obscure but seemingly relate to the dramatically changing ecosystem of the region due in part to climate as well as recovery among previously depleted upper trophic level species. Our results are also consistent with trends reported in seabirds that feed on juveniles of these notothenioids: decrease in the areas commercially fished. Under the regulation of CCAMLR, commercial fishing for finfish in the South Shetland Islands region (FAO Subarea 48.1) remains prohibited since 1991; results indicate that it cannot be reinstated. Fil: Barrera Oro, Esteban. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Marschoff, Enrique Ricardo. Ministerio de ...